Arrhythmia burden and related outcomes in Eisenmenger syndrome. (19th May 2017) - Baskar, Shankar; Horne, Philippa; Fitzsimmons, Samantha; Khoury, Philip R.; Vettukattill, Joseph; Niwa, Koichiro; Agaki, Teiji; Spence, Mark; Sakazaki, Hisanori; Veldtman, Gruschen
Abstract: Background: Patients with Eisenmenger syndrome have a shorter lifespan than the general population. A significant proportion develop arrhythmia and some, sudden death. Objective: The aims of this study were to characterize the frequency, type and effects of arrhythmias in adult patients with Eisenmenger's syndrome and to identify risk factors for arrhythmias. Methods: This retrospective study included patients aged ≥ 18 years of age with Eisenmenger's syndrome from three institutions. Arrhythmias were noted from electrocardiograms and Holter study reviews. Results: A total of 167 patients, 96 females, 63 males (gender not available in 9 patients) were included in this study. The mean age was 38 ± 9 years (range: 18–63 years) with a majority in NYHA functional class II or III (57% and 32% respectively). Twenty‐eight patients (17%) had significant tachyarrhythmia: paroxysmal supraventricular tachycardia (8 patients, 29%), atrial fibrillation (6 patients, 21%), atrial fibrillation and flutter (2 patients, 7%), nonsustained ventricular tachycardia (6 patients, 21%) and sustained ventricular tachycardia (6 patients, 21%). Among the entire study group, 26 patients (16%) were currently on antiarrhythmic therapy and 77 patients (49%) were on advanced therapies for pulmonary hypertension. Down syndrome was present in 78 patients (46%). There were 21 (13%) documented deaths, of which 8 (5%) were sudden death. Patients with arrhythmia were older [ P  = .01] and were more likely to have atrioventricular valvar regurgitation [Odds ratio: 4.33]. Advanced pulmonary hypertension therapy was associated with decreased all‐cause mortality in logistic regression analysis [odds ratio: 0.31], while antiarrhythmic therapy was associated with sudden death [odds ratio: 6.24]. Conclusions: Arrhythmias are common among patients with Eisenmenger syndrome occurring in around 1 in 5 individuals and are associated with all‐cause mortality and sudden death.